2023
DOI: 10.1080/15622975.2023.2203231
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of optical coherence tomography studies in schizophrenia, bipolar disorder and major depressive disorder

Abstract: Objectives: Due to the common neurodevelopmental origin and easy accessibility, the retina serves as a surrogate marker for changes in the brain. Hence, Optical Coherence Tomography (OCT), a tool to examine the neuronal layers of retina has gained importance in investigating psychiatric disorders. Several studies in the last decade have reported retinal structural alterations in schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD). However, the findings are inconsistent. Hence, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…These may explain the localized mfERG functional differences reported in schizophrenia, with normal PERGs that are summed over a larger macular area and are not sensitive enough to be altered by foveal changes ( Bernardin et al, 2021 ). Nonetheless there is promise that structural and functional changes may help to diagnose and monitor individuals with schizophrenia ( Silverstein et al, 2020 ; Prasannakumar, 2023 ) as well as helping to identify individuals at risk of developing schizophrenia ( Demmin et al, 2018 ; Hosak et al, 2018 ; Hébert et al, 2020 ; Komatsu et al, 2022 ; Maziade et al, 2022 ; Moreau et al, 2022 ; Peredo et al, 2022 ). Taken together, these functional and structural findings suggest that retinal biomarkers will become a useful clinical tool in the identification of individuals at risk of and with schizophrenia to improve management and early diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…These may explain the localized mfERG functional differences reported in schizophrenia, with normal PERGs that are summed over a larger macular area and are not sensitive enough to be altered by foveal changes ( Bernardin et al, 2021 ). Nonetheless there is promise that structural and functional changes may help to diagnose and monitor individuals with schizophrenia ( Silverstein et al, 2020 ; Prasannakumar, 2023 ) as well as helping to identify individuals at risk of developing schizophrenia ( Demmin et al, 2018 ; Hosak et al, 2018 ; Hébert et al, 2020 ; Komatsu et al, 2022 ; Maziade et al, 2022 ; Moreau et al, 2022 ; Peredo et al, 2022 ). Taken together, these functional and structural findings suggest that retinal biomarkers will become a useful clinical tool in the identification of individuals at risk of and with schizophrenia to improve management and early diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that people with bipolar disorder (or bipolar disorder traits) exhibit altered, state-dependent pupillary responses to light ( Bullock et al , 2019 ; Madsen et al , 2021 ) and reduced colour discrimination ( Fernandes et al , 2017 ; Fernandes et al , 2022 ; Garcia-Martin et al , 2019 ) and visual processing ( Fernandes et al , 2019 ), indicative of alterations in retinal sensitivity. Further to these functional changes, retinal imaging studies have found structural changes to the vasculature and retinal layers in individuals with bipolar disorder ( Appaji et al , 2019 ; Garcia-Martin et al , 2019 ; Prasannakumar et al , 2023 ). It is not known whether, and how, these structural and visual function changes relate to non-visual responses in bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 These standard clinical normative databases, however, are typically constrained to age-and race/ ethnicity-adjustment, overlooking many other potentially confounding factors. In the emerging field of oculomics, which studies the interplay between the eye and the body, 4,5 much attention has been directed towards the relationship between retinal measures and systemic diseases, particularly including metabolic, 6 mental, 7,8 nervous system [9][10][11] and cardiovascular factors. 12,13 Thus far, the literature has largely ignored the interaction between the retina and other body systems, as well as other potential interactions with physiology, demographics and pharmaceutical drug use.…”
Section: Introductionmentioning
confidence: 99%